2002
DOI: 10.1592/phco.22.17.1533.34127
|View full text |Cite
|
Sign up to set email alerts
|

Improving Blood Pressure Control in a Pharmacist‐Managed Hypertension Clinic

Abstract: Pharmaceutical care improves blood pressure control and results in more patients with hypertension reaching their blood pressure goal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
126
0
5

Year Published

2008
2008
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(145 citation statements)
references
References 17 publications
(13 reference statements)
9
126
0
5
Order By: Relevance
“…According to the data in Table 4, all items in CG were improved when compared with themselves six months ago, although, very obviously less than that in IG. Since, the two groups benefited from the same status quo of our social progress, respectively, an additional improvement in IG should be mainly attributed to the interventions of pharmacist with expertise and experience in drug therapy and participation in our outpatient clinic (Vivian, 2002). In our study, pharmacist conducted a total number of 192 medicative recommendations for drug therapy in IG, in which "Added a new antihypertensive drug" and "Increased dose" were the most frequent practice, accounting for 82 (42.7%) and 51 (26.6%).…”
Section: Discussionmentioning
confidence: 99%
“…According to the data in Table 4, all items in CG were improved when compared with themselves six months ago, although, very obviously less than that in IG. Since, the two groups benefited from the same status quo of our social progress, respectively, an additional improvement in IG should be mainly attributed to the interventions of pharmacist with expertise and experience in drug therapy and participation in our outpatient clinic (Vivian, 2002). In our study, pharmacist conducted a total number of 192 medicative recommendations for drug therapy in IG, in which "Added a new antihypertensive drug" and "Increased dose" were the most frequent practice, accounting for 82 (42.7%) and 51 (26.6%).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed the positive results of interventions, leading to the solution and prevention of DTP, reduction of treatment costs and satisfaction with Pharmaceutical Care program (Lee et al, 2006;Lyra Jr. et al, 2005;Vivian, 2002, Bernsten et al, 2001.…”
Section: Evaluation Of Pharmaceutical Care Interventionmentioning
confidence: 99%
“…In other countries, previous research have shown that pharmacist involvement in the ambulatorial care of hypertensive patients improves BP control (Lee et al, 2006;Zillich et al, 2005;Vivian, 2002;Mehos et al, 2000). Although, primary care units are the entrance of SUS, it almost does not have studies published about Pharmaceutical Care practice in Brazil (Lyra Jr. et al, 2007;Souza et al, 2007;Castro et al, 2006;Lyra Jr. et al, 2005;Oliveira et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Randomized clinical trials have demonstrated that non-physician clinicians are more effective at bringing hypertensive individuals in concordance with national guideline goals (41)(42)(43)(44)(45). One mechanism for the success of nurses in improving BP control relates to their training to address non-pharmacological interventions.…”
Section: Theoretical Frameworkmentioning
confidence: 99%